Development of a Website-Based Rubber Tender System for Cooperatives Tanjung Telang Village - Wijaya, Khana; Kartina, Riza (LPPM Universitas Bina Sarana Informatika, 2024)
The development of technology in today's modern era is progressing very rapidly, where everyone can find various technologies in various fields around human life, one of which is information technology. The existence of information technology can simplify and speed up data processing, information technology that is often used by an agency or organization is information system technology. Tanjung Telang Village Cooperative is a village engaged in processing and selling rubber residents. Currently, the promotional process carried out by the Village Cooperative only uses via telephone, resulting in very limited competition for the sale of rubber residents. The purpose of this research is to build a website-based rubber tender system that is expected to be more efficient and transparent to residents. This research uses descriptive quantitative and uses User Centered Design (UCD) system development. And the results obtained in this research are the creation of an online-based tender system that can be used by the Tanjung Telang Village Cooperative in the auction process to prospective buyers in the South Sumatra region.